Squaraine‐Based Polymers: Toward Optimized Structures for Optoelectronic Devices. Issue 13 (6th April 2017) - Broggi, Alessandra; Kim, Hyungsug; Jung, Jihye; Bracciale, Maria Paola; Santarelli, Maria Laura; Kim, Choongik; Marrocchi, Assunta
Abstract : A novel polymer semiconductor based on squaric acid is successfully prepared through polycondensation reaction. Newly developed polysquaraine is active as p‐channel semiconductor in thin‐film transistors showing decent p‐type mobility up to 5 × 10 −4 cm2 V −1 s −1 . Bulk heterojunction solar cells with power conversion efficiency up to 0.86% are also fabricated from the blends of polysquaraine and fullerene derivative PC71 BM. Abstract : A novel polymer semiconductor based on squaric acid is successfully prepared through polycondensation reaction. Physicochemical properties of polysquaraine are explored by Fourier transform infrared (FT‐IR) and ultraviolet‐visible (UV‐vis) absorption spectroscopy, thermogravimetric/modulated temperature differential scanning calorimetry (TGA/MTDSC) analyses, and cyclic voltammetry (CV). Next, the charge carrier properties are investigated through the fabrication and characterization of field‐effect transistors (FETs) using solution‐processed polymeric films. It is found that the polysquaraine is FET active and exhibits decent p‐type mobilities (up to 5 × 10 −4 cm 2 V −1 s −1 ), which illustrates the promising properties of this semiconductor in optoelectronics. Notably, there is no precedent for the use of squaraine‐based polymers in field‐effect transistors. Bulk heterojunction solar cells (BHJ‐OSCs) are finally prepared from the blends of polysquaraine with the fullerene derivative [6, 6]‐phenyl‐C71 ‐butyric acid methyl ester (PC71 BM). Power conversion efficiencies up to 0.86% are achieved for nonoptimized system under simulated air mass 1.5 (AM1.5) conditions.